Assessing Washing Methods for Reduction of Pesticide Residues in Green Leafy Vegetables - Khagi, Sajana (Khwopa Journal, 2023)
The use and import of pesticides have been increasing each year to increase agricultural production. The most highly consumed pesticide in Nepal is fungicide followed by insecticide, herbicide and others. Exposure to these pesticides may result in serious health effects. The main route of exposure is the consumption of contaminated fruits and vegetables. Many studies have shown to reduce the pesticide residues level through various culinary and processing treatments. This experiment was carried out to compare the effectiveness of four washing methods to reduce pesticide residues in vegetables. These comprised of running water method, washing by using NaHCO3, NaCl, and vinegar solution. The leafy vegetable samples, Bok choy (N=61) were purchased from local markets and analyzed for the contents of the two pesticides, 2,4-D and atrazine. Samples were extracted using Quick, Easy, Cheap, Effective, Rugged, and Safe (QuEChERS) method and analyzed by liquid chromatography coupled with tandem mass spectrometry (LC-MS/MS) with stable isotopically-labelled internal standards. The quality of the method was examined in terms of accuracy, precision, linearity, limit of detection (LOD) and limit of quantification (LOQ). Washing vegetables under running tap water significantly decreased (p<0.05) 2,4-D residues by 50%. However, atrazine residues were not reduced significantly from washing under running water but washing with vinegar had a significant effect. This study suggests that washing vegetables before consumption is important to reduce intake of pesticides and associated health risks.